End-of-life decisions in acute stroke patients: an observational cohort study. Issue 1 (December 2016) - Alonso, Angelika; Ebert, Anne; Dörr, Dorothee; Buchheidt, Dieter; Hennerici, Michael; Szabo, Kristina
Abstract Background Crucial issues of modern stroke care include best practice end-of-life-decision (EOLD)-making procedures and the provision of high-quality palliative care for dying stroke patients. Methods We retrospectively analyzed records of those patients who died over a 4-year period (2011–2014) on our Stroke Unit concerning EOLD, focusing on the factors that most probably guided decisions to induce limitation of life-sustaining therapy and subsequently end-of-life-care procedures thereafter. Results Of all patients treated at our Stroke Unit, 120 (2.71 %) died. In 101 (86.3 %), a do-not-resuscitate-order (DNRO) was made during early treatment. A decision to withdraw/withhold further life supportive therapy was made in 40 patients (34.2 %) after a mean of 5.0 days (range 0–29). Overall patient death occurred after a mean time of 7.0 days (range 1–30) and 2.6 days after therapy restrictions. Disturbance of consciousness at presentation, dysphagia on day 1 and large supratentorial stroke were possible indicators of decisions to therapeutic withdrawing/withholding. Proceedings of EOL care in these patients were heterogeneous; in most cases monitoring (95 %), medical procedures (90 %), oral medication (88 %), parenteral nutrition (98 %) and antibiotic therapy (86 %) were either not ordered or withdrawn, however IV fluids were continued in all patients. Conclusions A high percentage of stroke patients were rated as terminally ill and died in the course of caregiving. Disturbance of consciousness at presentation, dysphagia on day 1 and large supratentorial stroke facilitated decisions to change therapeutic goals thus initiating end-of-life-care. However, there is further need to foster research on this field in order to ameliorate outcome prognostication, to understand the dynamics of EOLD-making procedures and to educate staff to provide high-quality patient-centred palliative care in stroke medicine.